In vitro effects of tamoxifen on adipose‐derived stem cells. Issue 5 (14th July 2015) - Pike, Steven; Zhang, Ping; Wei, Zhengyu; Wu, Nan; Klinger, Aaron; Chang, Shaohua; Jones, Robert; Carpenter, Jeffrey; Brown, Spencer A; DiMuzio, Paul; Tulenko, Thomas; Liu, Yuan
ABSTRACT In breast reconstructive procedures, adipose‐derived stem cells (ASCs) that are present in clinical fat grafting isolates are considered to play the main role in improving wound healing. In patients following chemotherapy for breast cancer, poor soft tissue wound healing is a major problem. However, it is unclear if tamoxifen (TAM) as the most widely used hormonal therapeutic agent for breast cancer treatment, affects the ASCs and ultimately wound healing. This study evaluated whether TAM exposure to in vitro human ASCs modulate cellular functions. Human ASCs were isolated and treated with TAM at various concentrations. The effects of TAM on cell cycle, cell viability and proliferation rates of ASCs were examined by growth curves, MTT assay and BrdU incorporation, respectively. Annexin V and JC‐1 Mitochondrial Membrane Potential assays were used to analyze ASC apoptosis rates. ASCs were cultured in derivative‐specific differentiation media with or without TAM (5 uM) for 3 weeks. Adipogenic and osteogenic differentiation levels were measured by quantitative RT‐PCR and histological staining. TAM has cytotoxic effects on human ASCs through apoptosis and inhibition of proliferation in dose‐ and time‐dependent manners. TAM treatment significantly down‐regulates the capacity of ASCs for adipogenic and osteogenic differentiation (p<0.05 vs. control), and inhibit the ability of the ASCs to subsequently formed cords in Matrigel. This study is the first findings to our knowledge that demonstrated that TAM inhibited ASC proliferation and multi‐lineage ASC differentiation rates. These results may provide insight into the role of TAM with associated poor soft tissue wound healing and decreased fat graft survival in cancer patients receiving TAM.